Analisis Perkembangan Produksi Tanaman di Indonesia - Sari Wulandari; Melisa Syafitri; Maysaroh Hasibuan; Vera Maytara (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Horticultural crops or green plants have a great possibility of increasing because they have a high monetary value and a truly open market potential, both locally and abroad. Capacity as a supplier of different nutrients, minerals, fiber and blends for healthful satisfaction. As a financial capacity, green harvest is a type of income for farmers, traders and industry. With the many elements of green plants as will be described, there are also inhibiting elements that cause agricultural crops to not develop ideally, this is due to one element of disease. The strategy used in this paper is a subjective technique, with library research procedures. The information used is from the Statistical Measurement Agency (BPS). In collecting information involves references related to the creation of plants in Indonesia. The agrarian business sector will contribute, among others, to job retention and the production of higher added value in the various items submitted. The sub-area of ​​agriculture that has a high possibility to be developed is the sub-area of ​​food crops. Keywords: natural resources, horticultural crops, crop yields, market potential